PENGARUH PERILAKU KEWIRAUSAHAAN TERHADAP KEMANDIRIAN PRIBADI (STUDI KASUS PADA PEDAGANG PAKAIAN PASAR ATJEH - Sulfitra -; Darmayanti - (Jurnal Ilmiah Manajemen Muhammadiyah Aceh, 2012)
The behaviour and attitude are strongly influenced by somebody’s traits and chracteristic. Good behaviour of entrepreneur will lead to righteousness, safety and raise one’s dignity. This independence is the first stage to reach company’s economic healthy. The objective of this study is to identify and analysis the influence of entrepreneur’s behaviour to independence personality of Pasar Atjeh clothing merchants  by using minor personality type as variable which comprises of personal achieve, supersales person, real manager and expert idea generator. Data was gathered by interview, questionaire and study of documentation. Data was analysed by applying descriptive method and multiple linear regression. Data was processed statistically by using SPSS program verse 15.00 for windows to calculate F-test, T-test and determinant coefficient (R2). Purposive Sampling is used in this study as sampling technique.The result of this study shows that personal achiever, supersales person, real manager and expert idea generator has significant influence positively with the entrepreneur independence of Pasar Atjeh clothing merchant Banda Aceh.  With the value of determinant coefficient (R2 adjusted) is 0.654, the value of simultaneously F-test is 32,253 and significant at 0,000. Keywords: Entrepreneurship behavior, personality independence  and Aceh    Traditional Market